THE MODULATION OF MYOCARDIAL (DYS)FUNCTION AND REMODELING IN ISOPROTERENOL-TREATED RATS BY TESTOSTERONE. (June 2018) - Kovacova, D.; Rajkovicova, R.; Gubo, G.; Arendasova, K.; Barta, A.; Repova, K.; Simko, F.; Celec, P.; Paulis, L.
Abstract : Objective: The adrenergic overstimulation may contribute to myocardial damage and heart failure. Testosterone replacement therapy improved symptoms in men with heart failure. We investigated the progression of isoproterenol-induced myocardial damage with and without endogenous testosterone in male adult Wistar rats. Design and method: The animals were divided into control group and two heart failure groups: sham laparotomy and castrated. Heart failure was induced two weeks after sham/orchiectomy procedure by a single dose of isoprenaline (85 mg/kg, s.c .) or saline, respectively. After 8 weeks, MRI experiments and left ventricle catheterization in vivo and biochemical and histological evaluation ex vivo were performed. Results: Orchiectomy completely suppressed endogenous testosterone levels. In both, testosterone + and – animals, isoproterenol administration was associated with necrosis and reparative fibrosis leading to increased absolute and relative ventricle weight. The hypertrophy was ex vivo characterized to be inward in sham and outward in the castrated group. In vivo, in testosterone + animals there was non-significant hypertrophy with increased end-diastolic volume and peak filling rate. Increased left ventricular peak ejection rate, stroke volume and heart rate produced an augmented cardiac output. Similar changes were observed in rats after castration; yet increase in peak ejection rate and stroke volume were less pronounced. Pro-collagen 1a formation was more augmented in the sham-operated group. Conclusions: We conclude that in isoproterenol-induced damage, the akinetic myocardium was compensated by hyperkinetic activity of the unaffected heart muscle. The compensation of systolic function may be less pronounced in animals with lower testosterone levels tending to stiffness and diastolic dysfunction.